Comparison of solar radiation and PV generation variability: system dispersion in the UK. Issue 5 (27th April 2017) - Palmer, Diane; Koubli, Elena; Cole, Ian; Betts, Thomas; Gottschalg, Ralph
Abstract : This study investigates how the number and geographical distribution of solar installations may reduce aggregate irradiance variability and therefore lessen the overall impact of photovoltaic (PV) on grid distribution. The current distribution of UK solar farms is analysed. It is found that variability is linked to site clustering. Other factors may include distance and direction between sites, proximity to coast, local topography and weather patterns (i.e. wind, cloud etc.). These factors do not operate in isolation but form a complex and unpredictable system. The UK solar farm fleet currently comprises a range of system sizes which, when viewed en masse, reduces temporal variation in PV generation. The predominant southwest–northeast direction of solar farm groups is also beneficial in reducing output variability within grid supply point areas.